NASA'S Role in Aeronautics: A Workshop - National Research Council (The National Academies Press, 1981)
Keywords: Space and Aeronautics

Readiness Issues Related to Research in the Biological and Physical Sciences on the International Space Station (The National Academies Press, 2001)
Keywords: Space and Aeronautics

Capabilities for the Future: An Assessment of NASA Laboratories for Basic Research - National Research Council (The National Academies Press, 2010)
Over the past 5 years or more, there has been a steady and significant decrease in NASA's laboratory capabilities, including equipment, maintenance, and facility upgrades. This adversely affects the support of NASA's scientists, who rely on these capabilities, as well as NASA's ability to make the basic scientific and technical contributions that others depend on for programs of national importance. The fundamental research community at NASA has been severely impacted by the budget reductions that are responsible for this decrease in laboratory capabilities, and as a result NASA's ability to support even NASA's future goals is in serious jeopardy.
Keywords: Space and Aeronautics

Aging Avionics in Military Aircraft - National Research Council (The National Academies Press, 2001)
Extending the life of an airframe has proven challenging and costly. Extending the life of an avionics system, however, is one of the most critical and difficult aspects of extending total aircraft system lifetimes. Critical components go out of production or become obsolete, and many former suppliers of military-grade components have gone out of business. From 1986 to 1996, for example, the percentage of discontinued military/aerospace electronic devices nearly doubled—from 7.5 percent to 13.5 percent. In addition, legacy avionics systems, which were designed to meet requirements of the past, generally lack the full capability to perform new missions, meet new threats, or perform well in the new information-intensive battlefield environments. As the legacy aircraft fleet ages, avionics systems will become more and more difficult to support and maintain. Whereas the military once provided a large and profitable market for the electronics industry, the military electronics market today constitutes less than 1 percent of the commercial market. As a result, the military must increasingly rely on commercial off-the-shelf (COTS) technologies for its avionics hardware and software. Although COTS items are generally less expensive than comparable items designed especially to meet military specifications, the technology-refresh cycle for COTS is typically 18 months or less, which exacerbates the obsolescence problem for aircraft whose lifetimes are measured in decades. The short refresh cycle is driven mostly by the tremendous advances in computer systems, which comprise an increasing percentage of avionics content. In response to a request by the Assistant Secretary of the Air Force for Acquisition, the National Research Council convened the Committee on Aging Avionics in Military Aircraft, under the auspices of the Air Force Science and Technology Board, to conduct this study. This report summarizes the following:
Keywords: Space and Aeronautics

Thermionics Quo Vadis?: An Assessment of the DTRA's Advanced Thermionics Research and Development Program - National Research Council (The National Academies Press, 2001)
This report evaluates the Defense Threat Reduction Agency prior and present sponsored efforts; assess the present state of the art in thermionic energy conversion systems; assess the technical challenges to the development of viable thermionic energy conversion systems for both space and terrestrial applications; and recommend a prioritized set of objectives for a future research and development program for advanced thermionic systems for space and terrestrial applications.
Keywords: Space and Aeronautics

Managing Space Radiation Risk in the New Era of Space Exploration - National Research Council (The National Academies Press, 2008)
As part of the Vision for Space Exploration (VSE), NASA is planning for humans to revisit the Moon and someday go to Mars. An important consideration in this effort is protection against the exposure to space radiation. That radiation might result in severe long-term health consequences for astronauts on such missions if they are not adequately shielded. To help with these concerns, NASA asked the NRC to further the understanding of the risks of space radiation, to evaluate radiation shielding requirements, and recommend a strategic plan for developing appropriate mitigation capabilities. This book presents an assessment of current knowledge of the radiation environment; an examination of the effects of radiation on biological systems and mission equipment; an analysis of current plans for radiation protection; and a strategy for mitigating the risks to VSE astronauts.
Keywords: Space and Aeronautics

Maintaining U.S. Leadership in Aeronautics: Breakthrough Technologies to Meet Future Air and Space Transportation Needs and Goals - National Research Council (The National Academies Press, 1998)
After the completion of the National Research Council (NRC) report, Maintaining U.S. Leadership in Aeronautics: Scenario-Based Strategic Planning for NASA's Aeronautics Enterprise (1997), the National Aeronautics and Space Administration (NASA) Office of Aeronautics and Space Transportation Technology requested that the NRC remain involved in its strategic planning process by conducting a study to identify a short list of revolutionary or breakthrough technologies that could be critical to the 20 to 25 year future of aeronautics and space transportation. These technologies were to address the areas of need and opportunity identified in the above mentioned NRC report, which have been characterized by NASA's 10 goals (see Box ES-1) in "Aeronautics & Space Transportation Technology: Three Pillars for Success" (NASA, 1997). The present study would also examine the 10 goals to determine if they are likely to be achievable, either through evolutionary steps in technology or through the identification and application of breakthrough ideas, concepts, and technologies.
Keywords: Space and Aeronautics

Assessment of Directions in Microgravity and Physical Sciences Research at NASA - National Research Council (The National Academies Press, 2003)
For thirty years the NASA microgravity program has used space as a tool to study fundamental flow phenomena that are important to fields ranging from combustion science to biotechnology. This book assesses the past impact and current status of microgravity research programs in combustion, fluid dynamics, fundamental physics, and materials science and gives recommendations for promising topics of future research in each discipline. Guidance is given for setting priorities across disciplines by assessing each recommended topic in terms of the probability of its success and the magnitude of its potential impact on scientific knowledge and understanding; terrestrial applications and industry technology needs; and NASA technology needs. At NASA’s request, the book also contains an examination of emerging research fields such as nanotechnology and biophysics, and makes recommendations regarding topics that might be suitable for integration into NASA’s microgravity program.
Keywords: Space and Aeronautics

Microgravity Research in Support of Technologies for the Human Exploration and Development of Space and Planetary Bodies - National Research Council (The National Academies Press, 2000)
The frontier represented by the near solar system confronts humanity with intriguing challenges and opportunities. With the inception of the Human Exploration and Development of Space (HEDS) enterprise in 1995, NASA has acknowledged the opportunities and has accepted the very significant challenges. Microgravity Research in Support of Technologies for the Human Exploration and Development of Space and Planetary Bodies was commissioned by NASA to assist it in coordinating the scientific information relevant to anticipating, identifying, and solving the technical problems that must be addressed throughout the HEDS program over the coming decades. This report assesses scientific and related technological issues facing NASA's Human Exploration and Development of Space endeavor, looking specifically at mission enabling and enhancing technologies which, for development, require an improved understanding of fluid and material behavior in a reduced gravity environment.
Keywords: Space and Aeronautics

Decadal Survey of Civil Aeronautics: Foundation for the Future - National Research Council (The National Academies Press, 2006)
The U.S. air transportation system is very important for our economic well-being and national security. The nation is also the global leader in civil and military aeronautics, a position that needs to be maintained to help assure a strong future for the domestic and international air transportation system. Strong action is needed, however, to ensure that leadership role continues. To that end, the Congress and NASA requested the NRC to undertake a decadal survey of civil aeronautics research and technology (R&T) priorities that would help NASA fulfill its responsibility to preserve U.S. leadership in aeronautics technology. This report presents a set of strategic objectives for the next decade of R&T. It provides a set of high-priority R&T challenges—-characterized by five common themes—-for both NASA and non-NASA researchers, and an analysis of key barriers that must be overcome to reach the strategic objectives. The report also notes the importance of synergies between civil aeronautics R&T objectives and those of national security.
Keywords: Space and Aeronautics

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics

Space Nuclear Propulsion for Human Mars Exploration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Space Nuclear Propulsion for Human Mars Exploration identifies primary technical and programmatic challenges, merits, and risks for developing and demonstrating space nuclear propulsion technologies of interest to future exploration missions. This report presents key milestones and a top-level development and demonstration roadmap for performance nuclear thermal propulsion and nuclear electric propulsion systems and identifies missions that could be enabled by successful development of each technology.
Keywords: Space and Aeronautics

Factors Affecting the Utilization of the International Space Station for Research in the Biological and Physical Sciences - National Research Council (The National Academies Press, 2003)
Keywords: Space and Aeronautics

Microgravity Research Opportunities for the 1990s (The National Academies Press, 1995)
Keywords: Space and Aeronautics

Improving NASA's Technology for Space Science (The National Academies Press, 1993)
Keywords: Space and Aeronautics

Aeronautical Technologies for the Twenty-First Century - National Research Council (The National Academies Press, 1992)
Prepared at the request of NASA, Aeronautical Technologies for the Twenty-First Century presents steps to help prevent the erosion of U.S. dominance in the global aeronautics market. The book recommends the immediate expansion of research on advanced aircraft that travel at subsonic speeds and research on designs that will meet expected future demands for supersonic and short-haul aircraft, including helicopters, commuter aircraft, "tiltrotor," and other advanced vehicle designs. These recommendations are intended to address the needs of improved aircraft performance, greater capacity to handle passengers and cargo, lower cost and increased convenience of air travel, greater aircraft and air traffic management system safety, and reduced environmental impacts.
Keywords: Space and Aeronautics

Advanced Power Sources for Space Missions - National Research Council (The National Academies Press, 1989)
"Star Wars"—as the Strategic Defense Initiative (SDI) is dubbed—will require reliable sources of immense amounts of energy to power such advanced weapons as lasers and particle beams. Are such power sources available? This study says no, not yet—and points the way toward the kind of energy research and development that is needed to power SDI. Advanced Power Sources for Space Missions presents a comprehensive and objective view of SDI's unprecedented power requirements and the opportunities we have to meet them in a cost-effective manner.
Keywords: Space and Aeronautics

Toward a Microgravity Research Strategy (The National Academies Press, 1992)
Keywords: Space and Aeronautics

U.S. Supersonic Commercial Aircraft: Assessing NASA's High Speed Research Program - National Research Council (The National Academies Press, 1997)
The National Aeronautics and Space Administration (NASA) is currently developing advanced technologies to form the foundation for the next breakthrough in civil aviation: an economically viable, environmentally acceptable supersonic transport. NASA's High Speed Research Program works in conjunction with industry to identify and address critical technological challenges to initiating commercial development of a practical supersonic transport. The key technical areas investigated are engine emissions, fuel efficiency, service life, and weight; community noise; aircraft range and payload; and weight and service life of airframe structures. Areas of particular interest include the ability of technologies under development to meet program goals related to noise, emissions, service life, weight, range, and payload. This book examines aircraft design requirements, assesses the program's planning and progress, and recommends changes that will help the program achieve its overall objectives.
Keywords: Space and Aeronautics

Thriving in Space: Ensuring the Future of Biological and Physical Sciences Research: A Decadal Survey for 2023-2032 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Research in biological and physical sciences in space provides the critical scientific and technological foundations that make space exploration possible. As humanity looks towards the Moon and Mars for future missions, this work is needed to help astronauts adapt and live in the harsh environments of space. Thriving in Space provides a roadmap for increasing national investment in biological and physical science research, from experiments to infrastructure to education. This report identifies key scientific questions, priorities, and ambitious research campaigns that will enable human space exploration and transform our understanding of how the universe works. Thriving in Space reviews the state of knowledge in the current and emerging areas of space-related biological and physical sciences research and generates recommendations for a comprehensive vision and strategy for a decade of transformative science at the frontiers of biological and physical sciences research in space. This report will help NASA define and align biological and physical sciences research to uniquely advance scientific knowledge, meet human and robotic exploration mission needs, and provide terrestrial benefits.
Keywords: Space and Aeronautics